The effect of calcination on the hydroxyapatite structure - Šimková, Lenka; Šulcová, Petra (University of Pardubice, 2019)
The main objective of this work is the synthesis of hydroxyapatite powder with a general formula Ca10(PO4)6(OH)2 by the precipitation method with the following synthetic conditions: the Ca/P ratio = 1, the range of pH value = 7, where ammonia hydroxide solution was used to adjust the pH, and the rate of precipitation of ammonium dihydrogen phosphate was determined to 2 ml·min−1. Yet another aim of this paper was to characterize the physicochemical properties of the hydroxyapatite phase and subsequently to evaluate the effect of firing temperatures on the hydroxyapatite structure. The synthesized powder was characterized by X-ray diffraction (XRD) in order to identify the phase composition and crystallinity; the morphology of synthesized powder having been studied by scanning electron microscopy (SEM) and the prepared powder analyzed with respect to the particle size distribution (PSD).
Keywords: hydroxyapatite; precipitation; calcination; PSD; XRD; SEM